Small game species as bioindicators of the agri-environmental schemes -methodological overview - Szemethy, László; Keller, Norbert; Ujhegyi, Nikolett; Csányi, Sándor; Kovács, Imre; Patkó, László; Schally, Gergely; Tóth, Bálint; Biró, Zsolt (JOURNAL OF LANDSCAPE ECOLOGY, 2015)
Agri-environmental schemes were created in many European Union countries to mitigate the negative effects of intensive agriculture. Their efficiency is accompanied by serious professional debate, specifically concerning their economic impact. In Hungary, the first 5-year cycle of the local agri-environmental scheme (Agrár-környezetgazdálkodási Támogatási Rendszer ─ AKG), monitored by the Institute of Wildlife Conservation (commissioned by the National Food Chain Safety Office), has been completed. During this cycle, the brown hare (Lepus europaeus) was the indicator species. This species ─ as well as other small game species — is an excellent bioindicator of the agri-environmental projects, agro-ecosystems and extensive management methods of the area. The change in its population indicates the state of the population of many other ─ sometimes endangered and hardly detectable species. We analyzed the connection of the AKG and the populations of the small game species on both small and large spatial scales. Our small-scaled surveys included the approved population measuring and habitat use survey methods, and our large-scaled survey used the data of the Hungarian National Game Management Database and the data from the AKG field parcels. Analyzing these series, we recognized the true impact upon the AKG, and we developed a monitoring system, which can be used for other agri-environmental projects as well.